Effect of adenosine-1 receptor activation on pacemaker activity of interstitial cells of Cajal from mouse colon: Effects of adenosine on ICC - Choi, Seok; Lee, Jun Hyung; Shin, Dong Hoon; Wu, Wenhao; Huang, Xingyou; Hong, Chansik; Jun, Jae Yeoul (Cellular and Molecular Biology, 2023)
Adenosine plays an important role on gastrointestinal (GI) motility through adenosine receptors. Interstitial cells of Cajal (ICC) are pacemaker cells that regulate GI smooth muscle activity. The functional role and its signal mechanism of adenosine on the pacemaker activity were investigated using whole-cell patch clamp, RT-PCR, and intracellular Ca2+-imaging with ICC from mouse colon. Adenosine depolarized the membrane potentials and increased the pacemaker potential frequency, which was blocked by a selective A1-receptor antagonist, but not A2a-, A2b, or A3-receptor antagonist. A selective A1 receptor agonist represented similar effects as those of adenosine and mRNA transcript of A1-receptor was expressed in ICC. The adenosine-induced effects were blocked by phospholipase C (PLC) and a Ca2+-ATPase inhibitor. Adenosine increased spontaneous intracellular Ca2+ oscillations, as seen fluo4/AM. Both hyperpolarization-activated cyclic nucleotide (HCN) channel inhibitors and adenylate cyclase inhibitors blocked the adenosine-induced effects. And adenosine increased the basal cellular adenylate cyclase activity in colonic ICC. However, adenosine and adenylate cyclase inhibitors did not show any influence on pacemaker activity in small intestinal ICC for a comparison with that of the small intestine. These results suggest adenosine modulates the pacemaker potentials by acting HCN channels- and intracellular Ca2+- dependent mechanisms through A1-receptor. Therefore, adenosine may be a therapeutic target in colonic motility disorders.